Crystal Structure of Methyl (6-(2-Fluorobenzoyl)-5-Chloro-2-Benzoxazolinon-3-yl)-Acetate, C17H11ClFNO5 - Aydin, A.; Diindar, Y.; Akkurt, M.; Büyuk̈güngör, O.; Şahin, M.F. (My University, 2006)
C17H11ClFNO5, monoclinic, P121/c1 (no. 14), a = 7.489(5) Å, b = 18.367(5) Å, c = 11.752(5) Å, β = 94.222(5)°, V = 1612.1 Å3, Z = 4, Rgt(F) = 0.032, wRref(F2) = 0.083, T = 293 K. © 2014 Oldenbourg Wissenschaftsverlag GmbH, Rosenheimer Str. 145, 81671 München. All rights reserved.